Productivity growth and efficiency in the TRNC banking system - Kaya, Mustafa (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: This study aims to examine the productivity growth and the efficiency level of fifteen commercial banks operating in the Turkish Republic of Northern Cyprus (T.R.N.C.) banking industry during 2003-2011. Scale efficiency, technical efficiency and the decomposed productivity growth are measured by the non-parametric data envelopment analysis (DEA) and Malmquist productivity index (MPI). DEA results suggest that 66 % of the commercial banks in T.R.N.C. banking industry are scale inefficient and %73 of those scale inefficient banks are operating under decreasing returns to scale (DRS). Empirical results of DEA also revealed that on average TRNC banking industry is technically inefficient during the study period. Additionally, the decomposed total factor productivity growth shows that T.R.N.C. banking industry has achieved %1 growth in the productivity in the interval 2003-2011 which is mainly due to the technical efficiency change (%2) component rather than the regress in the technological (%1) component. The efficiency gain is attributed to scale efficiency rather than the pure efficiency component. Finally from the policy point of view, the results suggest that bank managers should increase the level of technology used in the commercial banks and imply better manager skills and specialization in the T.R.N.C. banking industry. Keywords: Productivity growth, data envelopment analysis, efficiency, Malmquist productivity index. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu çalısmanın amacı, 2003-2011 yılları arasında Kuzey Kıbrıs Türk Cumhuriyeti (K.K.T.C.) bankacılık sektöründe faaliyet gösteren on bes ticari bankanın etkinlik ve verimliligini incelemektir. Çalısmada ki ölçek etkinligi, teknik etkinlik ve ayrıstırılmıs veririmlilik artıs oranı parametrik olmayan veri zarflama analizi (VZA) ve Malmquist verimlilik endeksi ile ölçülmüstür. VZA sonuçları, K.K.T.C. bankacılık sektöründeki ticari bankaların %66’sının ölçek etkinsiz oldugunu ve bu ölçek etkinsiz bankalarında %73’unun ölçege göre azalan getiri ile faaliyet gösterdigi ortaya çıkmıstır. VZA ile elde edilen diger ampirik sonuçlarda ise, K.K.T.C. bankacılık sektörünün ortalama olarak, 2003-2011 yılları arasında teknik etkinsiz olarak faaliyet gösterdigi ortaya çıkmıstır. Bu sonuçlara ek olarak, Malmquist toplam faktör verimlilik endeksinden elde edilen bulgulara göre, K.K.T.C. bankacılık sektöründe bahsi geçen dönemler içerisinde %1’lik bir büyüme meydana gelmistir ve bu büyüme teknolojik olarak bankaların küçülmesine ragmen (%1) teknik etkinlikteki artıstan (%2) meydana gelmistir. Teknik etkinlikteki artıs ise banka personellerinin uzmanlasması ve banka yöneticelerinin stratejik uygulmalarından degil, daha çok ölçek etkinliginden meydana gelmistir. Elde edilen bulgular, K.K.T.C. bankacılık sektöründeki yöneticilerin bankaların teknoloji düzeyini arttırması ve daha üst düzey yöneticilik becerileri göstermeleri geretigini ortaya çıkarmıstır. Anahtar Kelimeler: Verimililik büyümesi, veri zarflama analizi, etkinlik, Malmquist verimlilik endeksi.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2013. Supervisor: Assoc. Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Banks and Banking - Cyprus (Turkish Republic of Northern Cyprus, 1983-); Productivity Growth, Data Envelopment Analysis, Efficiency, Malmquist Productivity Index